Assessment of the Role of Serum Ischemia modified Albumin in the early Diagnosis of Neonatal Sepsis - SABER A.M. EL-SAYED (International Journal of Pharma and Bio Sciences, 2018)
Neonatal sepsis (NS) still forms the most important and serious cause of morbidity and mortality outcome in the neonatal periods of infants, especially those who are preterm with very low birth weight and admitted for management in neonatal intensive care unit. The morbidity and mortality depends on the time of discovery of the infection and the course and speed of treatment. There are very high risks of mortality and morbidity due to difficulties in rapid diagnosis. If blood culture is positive NS is confirmed. But if the blood culture is negative, the physician cannot differentiate meningitis from sepsis clinically without lumbar puncture and CSF culture and sensitivity. Ischemia Modified Albumin (IMA) is a good discriminator between ischemic and non-ischemic newly born patients. Changes in IMA concentration has shown to occur during ischemic heart disease coronary induced ischemia. The aim of the study is to evaluate the role of serum ischemia modified albumin as a new modified marker for early diagnosis of neonatal sepsis and ischemia. The study was performed on two groups of patients: Group I (control group): consisted of 60 healthy new born babies (28 male, 32 female) subjects’ age mean being 36.00 weeks. These served as the control group. Group II (sepsis group): consisted of 60 new born babies diagnosed as infants with neonatal sepsis (30 male, 30 female) (the mean age being 32.60 weeks) . The study was carried out after obtaining acceptance from the attenders of all neonatal patients. The complete history, physical examination, laboratory investigations, full physical examination, full laboratory results (complete count of the blood, protein C-reactive and culture for the blood) and measurement of ischemia-modified albumin levels of all the neonatal babies were studied. The analysis of the results showed statistically significant difference in IMA between the control group and the sepsis group. The present study found no statistically significant difference in IMA between maturations in either full term or preterm infants with sepsis. This study revealed that the statistical difference between sexes of infants with sepsis was not significant. It was found that statistically there was no significant difference in IMA between living and dead septic neonatal outcome. Serum Ischemia Modified Albumin (IMA) levels are a good indicator between ischemic and non-ischemic newly born patients with sepsis at the time of diagnosis.